Parting Shots Undiplomatic diplomats - Parris, Mathew (London Penguin, 2011)
When leaving a foreign posting, Britain's ambassadors were encouraged to write a valedictory despatch until the practice was abolished in 2006. Unlike the usual style of the diplomatic bag, these last reports from foreign posts were unbuttoned, indiscreet and often very funny. There was much settling of scores, some poking fun of foreigners, a degree of moaning about the privations of Embassy life - and sometimes a bit of serious analysis too.
Includes index
Keywords: Diplomacy